Studi Teologis tentang Frasa “Injil Lain” dalam Galatia 1:6 dan Tantangan bagi Ortodoksi Masa Kini - Tjong, Andrew Lucas; Setyawan, Boris Bambang Rahadi (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
Amidst the numerous proclamations claiming to be the gospel of Christ, messages that deviate from the core of the Gospel of Christ while cloaked in the name of Christ and the Gospel itself, a proper understanding of the term “different gospel” becomes essential for the preservation of Christian doctrinal orthodoxy. This article explores the theological meaning of the phrase